2021
DOI: 10.1186/s43251-021-00050-x
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-art and annual progress of bridge engineering in 2020

Abstract: Bridge construction is one of the cores of traffic infrastructure construction. To better develop relevant bridge science, this paper introduces the main research progress in China and abroad in 2020 from 16 aspects. The content consists of four major categories in 16 aspects. The first part is about the bridge structure, including concrete bridge and high-performance materials, steel bridges, composite girders. The second part is about the bridge disaster prevention and mitigation, including bridge seismic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 336 publications
0
6
0
Order By: Relevance
“…The conclusions drawn from this study provide valuable guidance for practitioners in selecting the most appropriate BIM and GIS technologies for different aspects of bridge projects. Zhao et al [36] identified the major advances in bridge research both in China and internationally in 2020, covering 16 different aspects. The content is divided into four main categories.…”
Section: Bim Adoption In Complementary Road Structuresmentioning
confidence: 99%
“…The conclusions drawn from this study provide valuable guidance for practitioners in selecting the most appropriate BIM and GIS technologies for different aspects of bridge projects. Zhao et al [36] identified the major advances in bridge research both in China and internationally in 2020, covering 16 different aspects. The content is divided into four main categories.…”
Section: Bim Adoption In Complementary Road Structuresmentioning
confidence: 99%
“…UAV offers flexibility to practitioners because of the remote controls. Since the UAV can timely complete the detection work without disturbing the normal operation of the building, the monitoring and evaluation methods of the structural health of the building and the process of component maintenance are greatly improved [16]. Figure 1 shows the use of UAV to detect structural cracks.…”
Section: Intelligent Maintenancementioning
confidence: 99%
“…Since 2015, China has promulgated policies such as Made in China 2025 [25], the Guidance on Actively Promoting Internet+ Action [26], The National 13th Five-Year Plan for the Development of Strategic Emerging Industries [27], and the Next Generation Artificial Intelligence Development Plan [28], which have planned the key development directions of artificial intelligence in detail from various aspects and clearly stated that artificial intelligence is the core technology of the next round of scientific and technological revolution and industrial transformation. Through aligning the above policies, from 2015, related research has been conducted, such as the digitalization of shield tunnels [22], bridge informatization and intelligent bridges [29], intelligent geotechnical engineering [30], an intelligent construction-integrated management system [31], and the green construction of metro underground stations [32]. In the big data cluster, the main research topics include big data [14], internet+ [15], and intelligent management [10].…”
Section: Keyword Cluster Analysismentioning
confidence: 99%
“…The intelligence of bridges could not be achieved without the support of information. The research hotspots of bridge informatization and intelligent bridges in China are mainly focused on BIM plus technology, drones, inspection robots, and the deep learning of big data [29]. The introduction of information technologies, such as the IoT and cloud computing, has significantly improved the monitoring efficiency of bridges [24], in which machine works will replace manual human workers more often in carrying out traditional bridge structure inspections and long-term maintenance monitoring work.…”
Section: Bridge Informatizationmentioning
confidence: 99%